Legal Problems of Cigarette Excise Enforcement In Province East Java - Nurzeha, Suci Yaqiluh; Nashrullah, M Faiz (Universitas Trunojoyo Madura, 2024)
The high rate of active smoking in Indonesia has serious implications for public health and the country's economy. The Indonesian government has adopted a cigarette excise policy to reduce cigarette consumption and allocate excise revenue for law enforcement, public welfare, and public health through the concept of earmarking tax. This study aims to evaluate the effectiveness of cigarette excise law enforcement implementation in East Java Province, identify challenges faced, and provide recommendations for policy improvement. This research is an empirical juridical research using a descriptive qualitative approach. The primary and secondary data sources in this research are collected through interviews and documentation. The data analysis method used in this research uses the method formulated by Miles and Huberman, namely by reducing data, analyzing data, and drawing conclusions. The results showed that the implementation of regulations on the management of cigarette excise funds for law enforcement in East Java Province has not run optimally because there is a discrepancy between the allocation of funds stipulated in Minister of Finance Regulation Number 215/PMK.07/2021 and practices in the field. Local governments often allocate funds based on regional priorities that prioritize other sectors, resulting in inadequate funds for law enforcement.